Using Fairy Tale In Enhanced Spelling Learning of First High School Student In The City Of Manado - Monoarfa, S (Journal of Educational Method and Technology, 2019)
. The problem with this research is that teachers in teaching students focus more on improving teaching methods. They are more interested in choosing learning strategies such as inquiry, STAD, jigsaw, learning cell, and so on that emphasize the application of learning steps. The teachers forget their role as facilitators and creators who always facilitate students with teaching materials / materials as a result of the creation of teachers that have an impact on learning outcomes that are less than optimal. To solve this, the teacher needs to prepare a reading "stock" that can teach spelling while attracting students' interest in learning. Therefore the right reading material given is a fairy tale because the fairy tale is close to the child. The purpose of this study is to describe spelling learning, especially word writing, the use of punctuation, the use of capital letters through learning fairy tales in SMP Negeri 1 Manado students. The specific target to be achieved is the Science and Technology-Social and Culture products, scientific publications and textbooks about fairy tales in Indonesian that can be used as a means to teach enhanced spelling to students of SMP Negeri 1 Manado. This research method is a method of action study or action research. Reflection on actions is part of this method. The data source of this research is VII grade students of SMP Negeri I Manado. The research location is the city of Manado. To collect data, the techniques used are tests, observations (using field notes and rating checklists), and interviews. The procedure of conducting research is planning, implementing, observing, and reflecting. The results showed that VII grade students of SMP Negeri 1 Manado could be categorized as capable of using spelling because the average grade of the class obtained was 88.74%. The ability of students to use spelling, especially capital letters at the beginning of a sentence and a dot at the end of a sentence can be categorized as very capable because the results achieved by students are 100%.Â Keywords: use; fairy tales; spelling.